COMPARISON OF MOTHER’S PARENTING AND SOCIO-ECONOMIC PATTERNS ON STUNTING INCIDENTS IN THE WORKING AREA OF THE SUKA INDAH PUSKESMAS IN 2023 - Handayani, Puji; Galaupa, Resi (HEARTY, 2025)
Background:Every child has the right to get good nutrition. Children who receive good nutrition will grow and develop to their full potential.Stuntingis a condition of failure to thrive in infants (0-11 months) and toddlers (12-59 months) resulting from chronic malnutrition, especially in the first 1,000 days of life (HPK) so that children are too short for their age. Malnutrition occurs when the baby is in the womb and in the early days after the baby is born, but stunting only appears after the child is 2 years old.Stuntingoccurs in around 148.1 million (22.3%) children under five years of age in the world. Stunted toddlers in Asia have the highest prevalence in the world, namely around 52%.Toddlers experiencevarious child development problems such as motor delays, language, behavior, autism and hyperactivity.The socio-economic conditions of residence can also influence the prevalence of stuntingTo realize children’s development according to their age, parents must haveComparison of Parenting Patterns and Mother’s Socio-Economics on Stunting Incidents in the Suka Indah Community Health Center Work Area in 2023. Research purposes: This research was conducted to determine the comparison of mother’s parenting and socio-economic patterns in the incidence of stunting in the Suka Indah Community Health Center work area in 2023. Research methods: This research is a comparative descriptive research. The total sample was 31 parents who had stunted toddlers taken using purposive sampling technique. Parental parenting patterns use a questionnaire, while the development of stunted children is measured using the KMS. Statistical test using Chi-Square. Research result:The statistical test results obtained on maternal parenting patterns, namely the p value is 0.292, so it can be concluded that there is no relationship between maternal parenting patterns on the incidence of stunting in the Suka Indah Community Health Center Work Area in 2023. The statistical test results in the socio-economic category, namely the p value obtained is 0.329 > 0.05 so it can be concluded that there is no socio-economic relationship between the mother and the incidence of stunting in the Suka Indah Community Health Center Work Area in 2023. Conclusions and recommendations: There needs to be education and outreach to parentsstrive inprovide midwifery care for children and toddlers as well as families so that the incidence of stunting continues to decrease and decrease.